The Influence of Brand Image and Variety Seeking on Dana E-Wallet Brand Moving Through Consumer Satisfaction as an Intervening Variable in FEB UPN "Veteran" Jawa Timur Students - Huzaema, Maharani; Dermawan, Rizky; Azhar, Ratih Mukti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the impact of Brand image, variety-seeking behavior, and consumer satisfaction on the brand switching of the DANA e-wallet among students of the Faculty of Economics and Business at UPN "Veteran" East Java. This research employs a quantitative approach, involving 98 respondents. The sample was selected using a purposive sampling technique, with the criteria being students of FEB UPN "Veteran" East Java who had used DANA and afterward switched to another e-wallet. The analytical technique utilized in this study is Partial Least Squares (PLS), conducted through SmartPLS version 3.0 software, encompassing validity tests, reliability tests, and hypothesis testing. The findings indicate that brand image does not significantly affect brand switching, whereas variety-seeking behavior has a significant and positive impact. Furthermore, consumer satisfaction is demonstrated to mediate the relationship between Brand image and variety-seeking behavior in influencing brand switching.